(untitled) (Bangladesh Medical Journal, 2010)
Pre-eclampsia is one of the fatal complications in pregnancy. Zinc plays an important role in the course and eventual outcome of human pregnancy, and is essential for normal embryogenesis and fetal growth. Zinc deficiency in pregnancy is thought to be associated with pre-eclampsia. The aim of this study was, therefore, to investigate the scum zinc level in pre-eclampsia and to examine its association (if any) with pre-eclampsia. A case control study was done among 45 pre-eclamptic and 35 normotensive pregnants at their third trimester. Serum zinc concentration was determined by Atomic Absorption Flame Spectrophotometric method. Correlative analysis was made to find any correlation, of serum zinc with blood Pressure. Results showed identical Maternal and gestational age, and different gravida distribution for the patients and controls, and significantly (P<0.005) higher blood pressures (systolic and diastolic) for pre-eclampsia. Serum zinc concentration were estimated 0.65±0.09mg/L in pre-eclamsia and 0.60±0.08mg/L in pregnant controls, difference of which was insignificant (p=0.284). Correlative analysis wowed that there was a linear correlation between serum level and diastolic blood pressure, but it was found to be insignificant (r=0.158, p=0.330). It was suggested that changes in zinc status may not be an etiological or contributory factor in pre-eclamsia. Key words: Serum zinc; pre-eclampsia; diastolic blood pressure DOI: 10.3329/bmj.v39i1.6226 Bangladesh Medical Journal 2010; 39(1): 7-10